2002
DOI: 10.1177/107110070202300703
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Motor Performance of the Foot After Achilles Rupture Repair: A Randomized Clinical Study about Early Functional Treatment vs. Early Immobilization of Achilles Tendon in Tension

Abstract: The purpose of the study was to examine the recovery of some motor performance aspects of the lower extremity after Achilles tendon (AT) rupture repair by early functional postoperative treatment and early postoperative immobilization of the AT in tension in the early phase of recovery. The measured motor performance aspects were reaction time, speed of movement, foot tapping speed and coordination. The study population comprised 30 patients operated on for an acute, complete, closed AT rupture. The surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
0
16
0
3
Order By: Relevance
“…The bracing group comprised 281 patients and the casting group, 289 patients. Two RCTs were excluded from the meta-analysis because they did not address the outcomes specified for the review 30 31. Another RCT was excluded because the length of intervention in the functional rehabilitation group was 2 weeks 32.…”
Section: Resultsmentioning
confidence: 99%
“…The bracing group comprised 281 patients and the casting group, 289 patients. Two RCTs were excluded from the meta-analysis because they did not address the outcomes specified for the review 30 31. Another RCT was excluded because the length of intervention in the functional rehabilitation group was 2 weeks 32.…”
Section: Resultsmentioning
confidence: 99%
“…Kauranen y col. evaluó varios aspectos del rendimiento del motor (42). Los autores no pudieron identificar cualquier diferencia significativa para el rendimiento del motor.…”
Section: Discussionunclassified
“…Kauranen y col. de nuevo permitió el apoyo completo después de tres semanas en ambos grupos (42). El parámetro de resultado principal fue el rendimiento motor medido por el tiempo de reacción, la velocidad de movimiento y la coordinación.…”
Section: Temprana Movilizacion Del Tobillo (Tmt) Versus Inmovilizacióunclassified
See 1 more Smart Citation
“…Two randomised controlled trials compared this regimen to standard post-operative immobilisation in surgically treated ATR. One found isokinetic calf muscle strength to be better in the early motion group (79), but the other found no difference (80). Both of these trials only allowed weight bearing to begin after three weeks, but two smaller trials have shown some functional improvements from earlier mobilisation and weight bearing in a standard cast (81,82).…”
Section: Achilles Tendon Rupturementioning
confidence: 99%